I-listeningar / Mohamad Hasfee Dr. Hj. Shafee ... [et al.] - Dr. Hj. Shafee, Hasfee; Inche' Ibrahim, Mohd Shamil Azhan; Abdullah, Zuhaizi; Abdullah, Nor Azma (2020)
Facing the new generation, which is considered as a 21st-century learner, educators face a challenging transition in teaching. In the 20th century, teachers were respected because of their knowledge. This is because they are living in the era known as "the knowledge economy" stated by Peter Drucker. Other factors that may play a role towards limiting the teacher’s approach might be because of the law, district administration or the federal guidelines and in order to create creative learning, these factors need to be overcome [8]. In the 21st century, teachers must tune their approach towards what will they do with what they know, in other words, to innovate. The rapid development of technology, such as social media, had an adverse effect on listening skills. Looking at this concern, our group wanted to improve the listening approach to the students with i-ListeningAR. The group of students who involved in the usage of i-ListeningAR showed positive acceptance towards using this app.